Pengaruh Ease of Use, Brand Image, dan Word of Mouth Terhadap Loyalitas Pelanggan Layanan Jasa Transportasi Maxim - Anita Wahyuni; Nora Pitri Nainggolan (Komunitas Dosen Indonesia, 2024)
This study aims to prove the effects of each variables, namely ease of use, brand image, and Word of mouth on customer loyalty in which the decision to use services becomes an intervening variable. Based on previous research still said to be the supporting theory put forward by experts using the SPSS program as a statistical data processing tool. This type of research associative research. In this study, researched used non probability sampling techniques because researchers didn’t know the total number of members of the population studied. While the sampling technique used in this study is accidental sampling. While the population is all users of Maxim transportation in Batam City, the sample is 100 consumers of Maxim transportation users in Tiban Indah District, Batam City, with data analyses techniques used path analysis. The data processing used path analyses, its proven that ease of use, brand image and Word of mouth have no effect on customers loyalty for Maxim's online transportation services. On the results of the t test that partially Ease of use and brand image have no effects on customer loyalty, while Word of mouth has a significant effect on customer loyalty.